PERAN DAN FUNGSI KELUARGA DALAM MEMBANGUN KEPRIBADIAN REMAJA YANG BAIK DAN BERKELANJUTAN DI INDONESIA: SUATU TINJAUAN LITERATUR: THE ROLE AND FUNCTIONS OF THE FAMILY IN BUILDING GOOD AND SUSTAINABLE PERSONALITY OF YOUTH IN INDONESIA: A LITERATURE REVIEW - Syahrul Faidzin (Journal of Sustainable Development Issues, 2022)
This research is motivated by the youth nowadays issue, where the building of youth personality begins in the family environment. In the family environment, many factors make today's youth less moral, such as families who are regardless and do not care about each other and the influence of peers who misbehave. The sophistication of technology is misused, so the factors for building a negative youth personality. In addition, the most significant factor affecting youth personality is their social environment and interaction, namely everything around the child and events that occur as well as conditions along with the child's education process and the environment interaction every day. Environmental situations and conditions strongly influence youth. The environment influences many excellent and lousy youth morals. In line with the times and advances in science and modern technology can cause shock and anxiety in adolescents. The youth often imagine how their life will be in the future. Based on the literature study, this study concludes that families can significantly reduce violence, crime, exploitation, and torture by understanding 2 (two) factors that influence personality building, internal and external factors. Internal factors come from within the youth, while external factors demonstrate outside the human person. Thus, the family must remain the main gate for developing youth conditions relevant to sustainable development goals.